Studi Tantangan dan Harapan Guru Geografi untuk Meningkatkan Kualitas Pembelajaran Daring di SMA - Muhammad Setiawan Kusmulyono; Rahmatul Karimah (STABN RADEN WIJAYA WONOGIRI, 2022)
The pandemic made important difference in the society of education in Indonesia. To protect the safety and health of participants and educators, a significant shift from face-to-face to distant learning is required. This alteration has an impact on participant-educator relationship, making distant learning less effective. One of the main reasons for the long distance learning problem was that the learning model was less inventive and resulted in lower motivation. This study used a qualitative approach to collect data from 34 geography teachers using an open questionnaire to investigate the challenges of remote learning and teachers' expectations for support from the government, school administrators, and geography MGMPs. To incorporate the findings, a thematic analysis was performed. The study's findings show that, aside from information technology, the most significant problem is the difficulty in establishing learning models due to the restricted capacity of human resources in schools.